(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2022)
This paper sets out the basics of Switched Reluctance Motor (SRM), its principle of operation and basic model. A simulation of SMR model in Simulink is presented and its operation is explained. This basic model od SRM operates with turn-on and turn-off angles of 45°C and 75°. Next, on the basic model of SRM in Simulink, changes were made in the converter turn-on and turn-off angles. The new characteristics of the motor were presented, and the conclusions were derived about the impact of variation of turn-on and turn-off angles on the motor’s characteristics. Also, a load of 50 Nm has been added to the unloaded basic model of SRM and the obtained operating characteristics of the motor are presented.